TINJAUAN YURIDIS PUTUSAN AKTA PERDAMAIAN DI PENGADILAN AGAMA SAMARINDA MENGENAI HAK ASUH ANAK DI BAWAH UMUR PASCA PERCERAIAN - Febri Safrian (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTEveryone desires that the marriage he undertakes to remain intact throughout his lifetime, but many marriages which are so painstakingly established have to end in a divorce. the husband and wife who are going to divorce need to consider the problem of the child who has been born in that marriage. In the case of divorce, it will have legal consequences for the child, especially in the custody of minors. This research uses the juridical normative method, namely research that refers to the legal norms contained in statutory regulations and court decisions from the Religious Courts regarding the peace deed decisions regarding the custody of minors after divorce. The court is passive, meaning that it is just waiting, the initiative to take legal remedies is entirely dependent on the parties who are in the case, the Religious Courts should be able to impose sanctions on one of the parties who do not implement what has been agreed in the peace deed, thus the Court can impose sanctions on the parties. who do not implement what has been agreed in the peace deed? If there is a violation, the aggrieved party can submit a new application to the Head of the Religious Court to determine the implementation of the contents of the peace deed decision. Keywords: Peace Deed, Child Custody